The effect of overtime working on burn out, engagement and intention to leave of manufacturing workers in Vietnam - Nguyễn, Thị Hải Yến (2020)
In the context of controversy surrounding the issue of increasing maximum overtime hour in Vietnam, the study was conducted to clarify the effects of overtime on workers' intention to leave their jobs. This research aims to explain the relationship between overtime hour, burnout, engagement and intention to leave organization. The study was conducted by online surveys targeting workers who are working in manufacturing companies in Vietnam. There were 465 responses, but only 139 valid questionnaires were selected for data analysis. Results obtained from linear and quadratic analysis have drawn conclusions about both positive and negative roles of working overtime hour. All 6 hypotheses describing relationships between 4 variables including working overtime hour, burnout, engagement and intention to leave organization are accepted. There are 4 hypotheses matching result from previous research in the Job demand resource model on the relationship between burn out, engagement and intention to leave. In addition, the study confirmed both the positive and negative roles of over time hour: Working overtime hour has positive relationship with burn out which lead to negative impact on employee well-being such as intention to leave; working overtime hour have quadratic relationship with engagement which reduce intention to leave. The findings may suggest managers to arrange and allocate overtime appropriately, as well as the government to introduce overtime laws and resolve existing disputes